THE INFLUENCE OF CAREER GUIDANCE SERVICES ON JOB READINESS OF CLASS XII ACCOUNTING EXPERTISE COMPETENCE - Desi Hardianti; Sukirno Sukirno (Jurnal Ilmiah Pesantren, 2017)
The phenomenon studied in this research is about the readiness of vocational school students in relation to the implementation of career guidance services in schools, the research problem was formulated as follows: “how is the infuence of career guidance services to the readiness of class XII students accounting expertise competence SMK Negeri 11 Bandung”. The purpose of this study is to describe the services of career guidance and readiness work and to determine the effect of career guidance services to job readiness of student class XII accounting expertise competence SMK Negeri 11 Bandung. The research method is descriptive verifcation, data collection techniques on job readiness and career guidance services at school using questionnaire instrument that has passed the validity test and reliability test. Number of members of the population is 129 students, the sample used proportionate random sampling technique that is as many as 93 respondents. Numerical scale model Questionnaire used in this research and data analysis is Pearson product moment correlation. The result of the research shows that student’s readiness is in very good category, with the highest percentage result in ability and willingness to work dimension of 86, 49%. With career guidance services at school are in good category of 72.59%, including self-understanding and self-assessment, working world knowledge, decision making and attitude, and career planning. The result of the correlation coeffcient calculation shows 0.607, which means there is a strong relationship between career guidance service and job readiness. While the calculation of the coeffcient of determination obtained by 36.9% means that career counseling services affect 36.9% readiness of a student’s work. The remaining 63.1% is infuenced by other factors such as physical and mental maturity, interest, talent, intelligence, job information and work experience that need to be further investigated. And from t-test calculation is obtained t statistic = 7, 2863> t table (α = 0, 05) = 1,662. That is, career guidance services have a positive effect on the readiness of work